An 80-year summer temperature history from the Xiao Dongkemadi ice core in the central Tibetan Plateau and its association with atmospheric circulation. (February 2015) - Li, Xiangying; Ding, Yongjian; Yu, Zhongbo; Mika, Sillanpää; Liu, Shiyin; Shangguan, Donghui; Lu, Chengyang
Highlights: The Xiao Dongkemadi ice core δ 18 O reveals an 80-yr summer temperature history in the central Tibetan Plateau. Summer temperature is related to global warming trends and became more intense in recent decades. Recent summer warming has led to obvious glacier shrinking and runoff increasing. A teleconnection of regional climate with climate parameters in the Indian and North Atlantic oceans is revealed. Abstract: The climate significance of oxygen isotopes from the central Tibetan Plateau (cTP) ice cores is a debated issue because of large scale atmospheric circulation. A high-resolution δ 18 O record was recovered from the Xiao Dongkemadi (XD) ice core, which expanded the spatial coverage of δ 18 O data in this region. Annual average δ 18 O correlated significantly with nearby MJJAS air temperatures, suggesting the δ 18 O can be used as a proxy to reconstruct regional climate change. The reconstructed temperature anomaly is related to the regional and global warming trends, and the greater warming amplitude since 1970s is related to the elevation dependency of the warming signal. The close relationship of the warming to variations in glacier mass balances and discharge reveal that recent warming has led to obvious glacier shrinkage and runoff increase. Correlation analysis suggests that monsoon and westerly moisture substantially influence the cTP ice core records, along with an increase in their level of contribution to the XD core accumulation in recent decades, and confirms a teleconnection of regional climate of the cTP ice cores with climate parameters in the Indian and North Atlantic Oceans.